Numerical simulation on CO2 geology storage based on transient electromagnetic theory - Yang, Haiyan; Sun, Menglang; Zhao, Haibo; Mohamed, Koulibaly; Xu, Yunlei; Che, Rongqi; Li, Zhenyang (Frontiers in Energy Research, 2024)
Carbon capture and its storage is widely recognized as one of the primary approaches for reducing anthropogenic carbon emissions. The role of geophysical investigation is then for the selection of a suitable site for the geological storage of CO2 and the monitoring of the injection and storage process. The monitoring of the dynamic process can both detect leakage and minimize leakage potentials. To achieve this goal, this paper suggested the use of transient electromagnetic 3D finite-difference method to help realize the geospatial quantification of in-situ CO2. First, the horizontal model and the deep saline aquifer inclined were developed to analyze the low resistivity response which is the characteristic of typical aquifers. Second, the geoelectrical modeling which demonstrates the changes at the time of the CO2 injection, can be used to examine the temporal variations in subsurface resistivity. Thus, the impact to the volumetric changes due to the CO2 injection can be quantified. The significance of the results of this study confirmed the potential of the development of efficient dynamic monitoring and boundary delineation strategies for CO2 geological storage. Finally, a geoelectrical model for leakage has been established to investigate the likely changes in the resistivity of the subsurface strata because of CO2 leakage, which is reflected in the transient electromagnetic response patterns along with the leakage paths. This contributes to the monitoring of CO2 leakage in real time as well as detecting the location of leakage. This paper provided the theorical support of the transient electromagnetic method which has the potential to capture the dynamic diffusion process of CO2 storage in a deep saline aquifer. Furthermore, it could be used to an efficient monitor of CO2 leakage and identify the leakage paths.